SOSIALISASI MENGENAI BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) SEBAGAI LEMBAGA PENYELESAIAN SENGKETA KONSUMEN DI LUAR PENGADILAN - Suwandono, Agus; Kusmayanti, Hazar (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2024)
The Consumer Dispute Settlement Agency (BPSK) is an institution established by the Consumer Protection Law tasked with handling and resolving consumer disputes. The purpose of this community service is to socialize the existence of BPSK as a consumer dispute resolution institution for the community, consumers, and business actors. The method used in community service through legal counseling to socialize the existence of BPSK is followed by focused discussions related to duties and authorities, as well as consumer dispute resolution mechanisms at BPSK. The results of this activity increase knowledge and understanding of the existence of BPSK as a consumer dispute resolution institution outside the court domiciled in the Regency / City. BPSK was formed to provide consumers access to resolve disputes quickly and cheaply with various conveniences for consumers to claim their rights as consumers based on the UUPK. Keywords: consumer, dispute resolution, socialization, consumer protection.